The Mediating Role of Organizational Dissent in the Relationship Between Organizational Silence and Organizational Alienation: A Study on Social Service Employees (Third Sector Social Economic Review, 2025)
The subject of this research is social service workers' perceptions of organizational silence, organizational alienation, and organizational dissent. Organizational behavior is among the least emphasized topics in social work, and studies addressing the functioning of social service organizations, the organizational behavior of employees, and their relationships with their organizations based on contemporary organizational behavior concepts and theories are insufficient to establish a comprehensive body of knowledge on the topic. However, an examination of the historical development of social service indicates that its practices are predominantly conducted within organized structures whose common purpose is to contribute to the well-being of society. This research has taken this issue as a problem area and has been designed to determine whether the levels of organizational silence and organizational alienation of social service employees of public institutions and organizations differ according to their perceptions of organizational dissent.This research tested a "research model" designed to examine the "mediation" role of organizational dissent in the relationship between organizational silence and organizational alienation. The results demonstrated a strong and positive relationship between organizational alienation and organizational silence, whereas organizational alienation was negatively and weakly related to organizational dissent. Organizational dissent was found to mediate the relationship between organizational silence and organizational alienation; in other words, it serves as a mediating variable that alleviates the adverse effects of organisational silence on organisational alienation. As organizational silence increases, so does organizational alienation. As the level of dissent within an organization escalates, first silence, then alienation, diminishes.
Keywords: Organizational Behavior; Organizational Silence; Organizational Alienation; Organizational Dissent; Social Work